Tata Kelola Administrasi Pertanahan di Kalurahan Banyuraden - Widyanti, Adhiva Prily; Sapardiyono, Sapardiyono; Supama, Yohanes (Sekolah Tinggi Pertanahan Nasional, 2025)
Functionally, land administration is carried out by the Ministry of ATR/BPN at the central level, the BPN Regional Office at the provincial level, and the Land Office at the district/city level. Land organization units do not reach the village level, so the land office needs to involve the village government to provide records of ownership of unregistered land. The implementation of land administration in Banyuraden Village includes archiving, recording letter registration numbers and dates, digitizing archives, and issuing letters as attachments to conversion applications. The village government that plays a role in organizing land administration is the hamlet, jagabaya, and lurah. Mapping the components that support the function of land administration is necessary for its implementation in the village to be more effective and efficient. The purpose of this study is to identify and map the components that support the function of land administration in Banyuraden Village. Data collection was carried out through interviews, observations, and documentation studies, which were then analyzed using descriptive qualitative methods. The results of the study show that the land policy framework includes policies for recording letter registration numbers and dates, land information infrastructure related to letter C books and digital village maps, and institutional arrangements related to the roles of hamlets and village heads. Secara fungsional administrasi pertanahan dilaksanakan oleh Kementerian ATR/BPN di tingkat pusat, Kantor Wilayah BPN di tingkat provinsi, dan Kantor Pertanahan di kabupaten/kota. Unit organisasi pertanahan tidak sampai ke kalurahan, sehingga kantor pertanahan perlu melibatkan pemerintah kalurahan untuk menyediakan catatan penguasaan atas tanah yang belum terdaftar. Pelaksanaan administrasi pertanahan di Kalurahan Banyuraden meliputi penyimpanan arsip, pencatatan nomor dan tanggal register surat, digitalisasi arsip, dan penerbitan surat untuk lampiran permohonan konversi. Pemerintah kalurahan yang berperan menyelenggarakan administrasi pertanahan adalah dukuh, jagabaya, dan lurah. Pemetaan komponen yang menopang fungsi administrasi pertanahan diperlukan agar pelaksanaan administrasi pertanahan di kalurahan lebih efektif dan efisien. Tujuan dari penelitian untuk mengidentifikasi dan memetakan komponen yang menopang fungsi administrasi pertanahan di Kalurahan Banyuraden. Pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi yang kemudian dianalisis dengan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa kerangka kebijakan pertanahan meliputi kebijakan pencatatan nomor dan tanggal register surat, infrastruktur informasi pertanahan berkaitan dengan buku letter C dan peta kalurahan digital, kemudian pengaturan kelembagaan berkaitan dengan peran dukuh, jagabaya, dan lurah.